Community School gardens: forging socio-educational spaces in and for sustainability (Foro de Educacion, 2015)
This paper presents an educational project focusing on the creation of a Network of community organic school gardens. The purpose is to show how such gardens are not only educational, but can become unifying elements of change and innovation in the school culture, allowing to educate in a more comprehensive and meaningful way, while training learners in key skills demanded by education for sustainable development. This educational aim is reached by implementing a methodology of participatory action research (PAR), based on dialogue and negotiation as the way for participants to reflect and give joint solution to different needs and problems that the project is proposing. Also, academics -coordinators of the project- apply the Service-Learning methodology to their university students. The experience presented in this project reports on a collaboration with the different institutions involved, an initial pilot project and a later network of community school gardens, following the guidelines for the introduction of sustainability in the curriculum (CADEP-CRUE, 2005). The main conclusion is that school gardens, designed to integrate the community, may constitute cross socio-educational spaces of great educational and social value, since they not only aim to improve the educational intervention, but also to promote a social culture committed to sustainability.